RٌHO MESON PRODUCTION IN PHOTON PROTON INTERACTION - Hamad, Khalid (Iraqi Journal of Science, 2024)
Calculation of cross section forρmeson production in real photon proton interactions has been carried out in terms of Regge theory. The amplitude of is used for calculating the coupling of the exchanged particle at the photon - vector meson vertex. We only need to replace the coupling of the pion to quarks by the coupling of the exchanged particle to quarks. This coupling has been fixed by the experimental data. A comparison of the model with data shows an excellent agreement.